STYLING AND TRANSFORMATION OF CLOTHES IN FASHION ILLUSTRATION WITH THE HELP OF ARTIFICIAL INTELLIGENCE IMAGE GENERATION SERVICES - STRYZHOVA, OKSANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The means of developing new clothing models – stylization and transformation – are informal, creative operations in clothing design that require a significant amount of time for their execution and visualization of the results. Also, the time spent at the stage of artistic design of clothes is directly affected by the linearity (graduality) of the creative strategy of the designer during the implementation of stylistic or morphological changes in the artistic solutions of the sketches. However, the modern pace of updating the model range of clothing for its production requires high-speed and productive work of the designer at the stage of artistic design. And therefore, simultaneity and multi-vector work on several ideas and artistic solutions is a way to significantly reduce development time. Such requirements require appropriate tools for visualizing design ideas, which could provide a significant reduction in time due to the simultaneous development of a large number of options and their diversity.Generative design deals with the problems of producing a large number of ideas under given conditions. For the generation of design objects, especially graphic ones, the use of image creation capabilities with the help of artificial intelligence is actively developing, which allows to reduce the time spent on visualizing ideas. Therefore, the research of AI services and image generation tools at the stage of artistic design of model sketches in fashion design is relevant. The article highlights the main results of an analytical study of the features of using the tools of generative services of neural networks with artificial intelligence at the stage of stylization and transformation of artistic solutions and visualization of their results when developing sketches of new clothing models and fashion illustrations.
Keywords: generation of fashion illustrations; generative clothing design; clothing styling; clothing transformation